THE POPULARIZATION OF PHYSICAL CULTURE AND SPORTS FOR PERSONS WITH DISABILITIES - A. Gonokhov; E. Domashova; I. Kurnosova (Вестник университета, 2019)
Some aspects of the legal framework, ensuring right of everyone to free access to sports and physical culture, including for persons with disabilities, have been considered. It has been noted, that for today there is a growing interest in adapted sports programs, which are aimed at people with disabilities and disabled people. Work with this category of the population should be based on ensuring prevention, control, assessment, restoration and safety of athletes with disabilities and disabled people; implementation of insurance bases of their social protection; planning of costs for training of athletes of the highest qualification, etc.